Pengaruh Algoritma Media Sosial Terhadap Selektivitas Konsumsi Berita Politik Pada Generasi Z Di Indonesia - Indiarta Raghda Atshila S; Callie Rizma Riendani; Afif Abhinaya; Ahmad Ridlo Abdillah; Bahy Dzaky Mufadhol (PT PUSTAKA CENDEKIA GROUP, 2024)
This research wants to find out how social media algorithms influence what political news is read by young people today, namely generation Z in Indonesia. We found that this algorithm makes young people more likely to only see news that aligns with their political opinions. So they have increasingly strong views on one side and find it difficult to accept different opinions. This is the same as if we only talk to people who have the same opinion as us, so we become less open to other people's views. This research is important, because it shows how serious we are in learning to be able to assess the truth of the news we read on social media, so that we are not easily influenced by wrong or biased information.